ANALYSIS OF SCENARIOS FOR INCREASING THE LEVEL OF ENERGY EFFICIENCY OF PUBLIC BUILDINGS WITH INTEGRATION OF RES - СУХОДУБ, І. О.; СЕРДЕЧНИЙ, П. Ю. (Technologies and Engineering, 2024)
Purpose. The study aims to investigate projects aimed at increasing the level of energy efficiency of public buildings using specialized software for dynamic energy modeling, DesignBuilder/EnergyPlus, for various levels of energy efficiency and integration of non-traditional and renewable energy sources. Methodology. In the process of researching the stated problem, the current regulatory framework of Ukraine, which describes and regulates approaches to assessing the energy efficiency of buildings and available software complexes, were analyzed. Proven specialized software for dynamic energy modeling of buildings (DesignBuilder/EnergyPlus) and non-traditional and renewable energy sources (PVSOL premium, TSOL) were used. Findings. During the research work, projects aimed at increasing the level of energy efficiency of a public building using different scenarios/levels of energy efficiency and integration of non-traditional and renewable energy sources were analyzed. The following scenarios were considered: actual, baseline, proposed, and enhanced proposed. For each scenario, indicators of final and primary energy consumption for heating, cooling, lighting, equipment, fans and pumps, hot water supply, as well as CO2 emissions and the potential for energy substitution from RES were analyzed. As a result of the implementation of measures provided for in the proposed scenario, the consumption of final energy can decrease by 58.6% compared to the baseline case, while the enhanced proposed scenario can increase these indicators to 62.6%. The coefficient of substitution of thermal energy by RES can be 22%, for electricity – 16% (enhanced proposed scenario). Scientific novelty. Dynamic energy modeling was used to calculate the level of energy efficiency of a public building for different scenarios, and modeling of the integration of non-traditional and renewable energy sources when replacing thermal and electrical energy was conducted. Practical value. As a result of the conducted research, the potential for saving final and primary energy, CO2 emissions when implementing various scenarios of projects aimed at increasing the level of energy efficiency and integrating RES was determined, allowing to make informed technical decisions during the comprehensive modernization of public buildings in Ukraine.